Efektifitas Buah Pepaya (Carica Papaya L.) dan Buah Semangka (Citrullus Lanatus.) Terhadap Kelancaran ASI Ibu Menyusui - Silvia Darmawati Kartika Sari; Agnes Isti Harjanti; Mudy Oktiningrum (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Breast milk (BM) is the optimal source of nutrition for newborns up to six months old, providing essential antibodies, complete nutrition, and easier digestion compared to formula milk. Exclusive breastfeeding is crucial for infant health, and efforts to support lactation include consuming a balanced and nutritious diet. This study aimed to examine the effect of papaya and watermelon consumption on breast milk expression in nursing mothers. The research utilized a true experimental design with a two-group post-test approach, conducted over five consecutive days. The intervention involved consuming 400 grams of cut papaya and 300 grams of watermelon daily. The study population consisted of postpartum mothers with infants aged 0–6 months, and the sampling technique used was probability sampling, resulting in a total of 42 respondents. Participants were divided into two groups: 21 in the control group and 21 in the intervention group. The Wilcoxon test was applied for statistical analysis. The findings revealed that papaya consumption significantly affected breast milk expression, with a p-value of 0.046 (<0.05), accepting the alternative hypothesis (Ha). This result indicated that papaya intervention increased breast milk expression by 2,000 times. Similarly, the watermelon intervention showed a significant effect, with a p-value of 0.02 (<0.05), also leading to the acceptance of the alternative hypothesis (Ha). The analysis suggested that watermelon consumption improved breast milk expression in nursing mothers by 3.162 times. These findings highlight the potential benefits of consuming papaya and watermelon in enhancing lactation, providing valuable insights for nursing mothers and healthcare professionals in supporting breastfeeding practices.